2012
DOI: 10.1097/sle.0b013e318247c02e
|View full text |Cite
|
Sign up to set email alerts
|

Postpolypectomy Bleeding

Abstract: Endoscopic polypectomy is at the forefront of colorectal cancer (CRC) prevention. However, endoscopic polypectomy is not completely free of complications, with bleeding being one of the most common complications encountered. In view of the ongoing campaign to introduce colorectal cancer screening to the population, addressing the issue of colonoscopic complications, and postpolypectomy bleeding (PPB) in particular is becoming more important. Despite the fact that the overall incidence of PPB is low, predisposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Of these, hemorrhage is the most common complication [5, 6, 7, 8, 9, 10]. Delayed hemorrhage following a polypectomy occurs between 3 to 7 days after the procedure, and its incidence is commonly reported to range between 0.6% and 0.9% [5, 6, 7, 8, 9]. Postpolypectomy delayed hemorrhage is unpredictable and can occur after hospital discharge; therefore, it requires attention.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, hemorrhage is the most common complication [5, 6, 7, 8, 9, 10]. Delayed hemorrhage following a polypectomy occurs between 3 to 7 days after the procedure, and its incidence is commonly reported to range between 0.6% and 0.9% [5, 6, 7, 8, 9]. Postpolypectomy delayed hemorrhage is unpredictable and can occur after hospital discharge; therefore, it requires attention.…”
Section: Introductionmentioning
confidence: 99%
“…Increased surveillance is recommended after polyps are found (7), further straining a medical system that already struggles to meet the demand for screening and diagnostic colonoscopies, both in terms of cost (8) and available providers (9). Additionally, colonoscopy and polypectomy are not without risk; colonic perforation occurs at a low but predictable rate during colonoscopy (10), and significant post-colonoscopy bleeding is more likely to occur after polypectomy (11). …”
Section: Introductionmentioning
confidence: 99%
“…Postpolypectomy bleeding (PPB) is the most common complication, with an incidence ranging from 0.6% to 8% in large series [1, 2, 3]. The incidence of PPB has been reported to depend on its definition: early, delayed, and overall [4]. …”
mentioning
confidence: 99%
“…Garcia et al [6] reported thromboembolic events in 0.7% of 1,293 patients with warfarin interruptions, and Blacker et al [7] reported that strokes occurred in 1% of 987 patients with atrial fibrillation after temporary anticoagulation discontinuation. Until now, 2014.30.4.157whether antiplatelet agents such as aspirin increase the risk of PPB has been debatable [4]. Among polyp-related factors associated with PPB, the size of the polyp, as Moon et al [8] showed in his retrospective study of the current issue, seems to have the most data supporting it.…”
mentioning
confidence: 99%
See 1 more Smart Citation